The Human NADPH Oxidase, Nox4, Regulates Cytoskeletal Organization in Two Cancer Cell Lines, HepG2 and SH-SY5Y - Auer, Simon; Rinnerthaler, Mark; Bischof, Johannes; Streubel, Maria Karolin; Breitenbach-Koller, Hannelore; Geisberger, Roland; Aigner, Elmar; Cadamuro, Janne; Richter, Klaus; Sopjani, Mentor; Haschke-Becher, Elisabeth; Felder, Thomas Klaus; et al. (Frontiers in Oncology, 2017)
NADPH oxidases of human cells are not only functional in defense against invading microorganisms and for oxidative reactions needed for specialized biosynthetic pathways but also during the past few years have been established as signaling modules. It has been shown that human Nox4 is expressed in most somatic cell types and produces hydrogen peroxide, which signals to remodel the actin cytoskeleton. This correlates well with the function of Yno1, the only NADPH oxidase of yeast cells. Using two established tumor cell lines, which are derived from hepatic and neuroblastoma tumors, respectively, we are showing here that in both tumor models Nox4 is expressed in the ER (like the yeast NADPH oxidase), where according to published literature, it produces hydrogen peroxide. Reducing this biochemical activity by downregulating Nox4 transcription leads to loss of F-actin stress fibers. This phenotype is reversible by adding hydrogen peroxide to the cells. The effect of the Nox4 silencer RNA is specific for this gene as it does not influence the expression of Nox2. In the case of the SH-SY5Y neuronal cell line, Nox4 inhibition leads to loss of cell mobility as measured in scratch assays. We propose that inhibition of Nox4 (which is known to be strongly expressed in many tumors) could be studied as a new target for cancer treatment, in particular for inhibition of metastasis.